Editor's Choice– Impact of identifying precipitating factors on 30-day mortality in acute heart failure patients. Issue 7 (October 2019) - Rossello, Xavier; Gil, Víctor; Escoda, Rosa; Jacob, Javier; Aguirre, Alfons; Martín-Sánchez, Francisco J; Llorens, Pere; Herrero Puente, Pablo; Rizzi, Miguel; Raposeiras-Roubín, Sergio; Wussler, Desiree; Müller, Christian E; et al.
Background: The aim of this study was to describe the prevalence and prognostic value of the most common triggering factors in acute heart failure. Methods: Patients with acute heart failure from 41 Spanish emergency departments were recruited consecutively in three time periods between 2011 and 2016. Precipitating factors were classified as: (a) unrecognized; (b) infection; (c) atrial fibrillation; (d) anaemia; (e) hypertension; (f) acute coronary syndrome; (g) non-adherence; and (h) two or more precipitant factors. Unadjusted and adjusted logistic regression models were used to assess the association between 30-day mortality and each precipitant factor. The risk of dying was further evaluated by week intervals over the 30-day follow-up to assess the period of higher vulnerability for each precipitant factor. Results: Approximately 69% of our 9999 patients presented with a triggering factor and 1002 died within the first 30 days (10.0%). The most prevalent factors were infection and atrial fibrillation. After adjusting for 11 known predictors, acute coronary syndrome was associated with higher 30-day mortality (odds ratio (OR) 1.87; 95% confidence interval (CI) 1.02–3.42), whereas atrial fibrillation (OR 0.75; 95% CI 0.56–0.94) and hypertension (OR 0.34; 95% CI 0.21–0.55) were significantly associated with better outcomes when compared to patients without precipitant. Patients with infection, anaemia and non-compliance were not at higher risk of dying within 30 days. These findings were consistent across gender and age groups. The 30-day mortality time pattern varied between and within precipitant factors. Conclusions: Precipitant factors in acute heart failure patients are prevalent and have a prognostic value regardless of the patient's gender and age. They can be managed with specific treatments and can sometimes be prevented.